The climatic debt is growing in the understorey of temperate forests: Stand characteristics matter. Issue 7 (7th May 2021) - Richard, Benoit; Dupouey, Jean‐Luc; Corcket, Emmanuel; Alard, Didier; Archaux, Frédéric; Aubert, Michaël; Boulanger, Vincent; Gillet, François; Langlois, Estelle; Macé, Sébastien; Montpied, Pierre; Beaufils, Thérèse; et al.
Abstract: Aim: Climate warming reshuffles biological assemblages towards less cold‐adapted but more warm‐adapted species, a process coined thermophilization. However, the velocity at which this process is happening generally lags behind the velocity of climate change, generating a climatic debt the temporal dynamics of which remain misunderstood. Relying on high‐resolution time series of vegetation data from a long‐term monitoring network of permanent forest plots, we aim at quantifying the temporal dynamics – up to a yearly resolution – of the climatic debt in the understorey of temperate forests before identifying the key determinants that modulate it. Location: France. Time period: 1995–2017. Taxa studied: Vascular plants. Methods: We used the community temperature index (CTI) to produce a time series of understorey plant community thermophilization, which we subsequently compared to a time series of mean annual temperature changes over the same period and for the same sites. The direction and magnitude of the difference (i.e., the climatic debt) was finally analysed using linear mixed‐effect models to assess the relative contributions of abiotic and biotic determinants, including forest stand characteristics. Results: We found a significant increase in CTI values over time (0.08–0.09 °C/decade), whereas the velocity of mean annual temperature changes was three times higher over the same period (0.22–0.28 °C/decade). Hence, the climatic debt increased over time and was greater in forest stands with higher basal area or older trees as well as under warmer macroclimate. By contrast, a greater frequency of anthropogenic disturbances decreased the climatic debt, while natural disturbances and herbivory had no impact. Conclusions: Although often overlooked in understanding the climatic debt of forest biodiversity, changes in forest stand characteristics may modulate the climatic debt by locally modifying microclimatic conditions. Notably, the buffering effect of the upper canopy layer implies microclimate dynamics that may provide more time for understorey plant communities to locally adapt.